Kafah Science Test Model to Improve the Quality of Prospective Teachers - Ayub, Syahrial; Rokhmat, Joni; Busyairi, Ahmad; Afifah, Gusti (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2023)
This research aims to create and analyze a comprehensive science question model (Science Kafah) to enhance the quality of prospective teachers. The quality of prospective teachers refers to their comprehensive abilities in a specific science subject being taught. These abilities encompass conceptual understanding, religious connections, application, and meaningfulness. The research instrument consists of Science Kafah questions with various developed models. The analysis is conducted on the question models and individual items to assess validity, reliability, discrimination power, and difficulty index. The research findings reveal that the Science Kafah question model consists of 1) questions measuring conceptual understanding, 2) questions measuring religious abilities, 3) questions measuring application skills, 4) questions measuring meaningfulness, and 5) questions measuring social skills. Analysis of the instrument shows that out of the 25 tested questions, 20% were deemed inadequate, while 80% met the criteria for good questions. The Science Kafah question model can assess comprehensive abilities in science, its connection to religion, application skills (technology, engineering, environment, arts, and mathematics), and the meaningfulness of the taught concepts.